CYBERCRIME DALAM ABAD 21 : SUATU PERSPEKTIF MENURUT HUKUM INTERNASIONAL - Sinta Dewi (Faculty of Law, Universitas Diponegoro, 2011)
The development of information technology has encouraged the development of rapid Demian use of the Internet to conduct transactions in the world. Today virtually all parties have used the Internet both for individuals, businesses and government agencies. However, the global Internet usage has led certain parties to commit crimes in cyberspace or cybercrime. Because of human activities in the cyber world is limitless activities that have an international dimension, the transnational nature of crimes committed so that when viewed from the global rate of loss has exceeded the crimes committed due to drug sales. To deal with this problem it is necessary that takes into account protection through regulatory harmonization Globally and will be able implementad in natiomal regulations. This research purpose are to analyze several legal issues such as how International Law Play an Important Role in Regulationd and urge international Cooperation to combat Cybercrime. This research used a normative juridical approach which focuses on secondary data, then used all the legal and juridical methods of historical comparison is obtained from the research literature is supported by primary data from field research. The specifications of research used is descriptive analytical and subsequent data collected were analyzed qualitatively. Based on the research and data analysis can be concluded that International Law has play an important role in regulating Cyberlaw and has promote international cooperation in combating Cybercrime and at the same time will encourage the harmonization of Cyberlaw Regulations.